Genetic diversity of Geophagus brasiliensis from the South American Atlantic Rainforest. (December 2017) - Azevedo, R.S.; Bitencourt, A.; Silva, D.A.; Amorim, A.; Mazzoni, R.; Carvalho, E.F.; Amaral, C.R.L.
Abstract: The Atlantic Rainforest is one of the global conservation hotspots, representing a seriously threatened area with high levels of endemism and species richness. The fishes from the Atlantic Rainforest are one of the most exploited vertebrate groups by the international aquarium commerce, with an annual trade volume of about U15-25 billions, now aggravated by the Internet e-Commerce and playing a crucial role on the sales and distribution of these species. The Cichlidae is one of the most exploited groups with several species being commonly sold in several online sites and aquarium stores all around the world. In this sense, our aim is to study the genetic diversity of the native cichlid Geophagus brasiliensis from the South American Atlantic Rainforest in Brazil. We constructed a database including 75 sequences from Geophagus brasiliensis from the Ubatiba river with 540 bp of the mtDNA D-loop region using primers H16498 and L15774M and conducted molecular analyses with Geneious v4.82, DnaSP v5, Arlequin v3.5 and PopART. Our results point show that although G. brasiliensis is considered as a territorialist species, which exhibits parental care and small movement rates, population genetic structure could not be observed along the sample area, suggesting the existence of considerable gene flow at least among the sampled populations.